ECONOMIC, ENVIRONMENTAL AND SOCIAL OPTIMIZATION OF PHOTOVOLTAIC IMPLEMENTATION IN COFFEE SHOP BUSINESSES, MALANG CITY - Febby Ayu Oktiviania; Aripriharta Aripriharta (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2024)
This research aims to optimize a hybrid photovoltaic (PV) energy system for a coffee shop business in Malang City by incorporating economic, environmental, and social dimensions. The optimization process employs the Queen Honeybee Migration (QHBM) algorithm, a multi-objective heuristic approach. Key performance indicators include Cost of Energy (COE), Carbon Emissions, Renewable Fraction (RF), and Community Acceptance, which is evaluated using the Technology Acceptance Model (TAM) through a structured questionnaire. The system is designed to meet a daily energy demand of 28.8 kWh, under an average solar irradiation of 3.86 kWh/m²/day. Simulation and optimization were conducted using Python-based programming. The results demonstrate that the optimal configuration consists of 20 solar panels (550 Wp) and 10 battery units (200 Ah), achieving a COE of IDR 320.04/kWh and an RF of 99.87%. Compared to conventional grid electricity, the proposed system offers significant cost savings and emission reductions. Furthermore, the TAM-based survey yielded an average acceptance score of 3.72, indicating a favorable public perception of hybrid PV system adoption in small business contexts.